Domestic waste (eggshells and banana peels particles) as sustainable and renewable resources for improving resin-based brakepad performance: Bibliometric literature review, techno-economic analysis, dual-sized reinforcing experiments, to comparison ... - Nandiyanto, Asep Bayu Dani; Ragadhita, Risti; Fiandini, Meli; Al Husaeni, Dwi Fitria; Al Husaeni, Dwi Novia; Fadhillah, Farid (Communications in Science and Technology, 2022)
The objective of this study is to develop a new environmentally-friendly brake pad made from eggshells (Es) and banana peels (BPs) as reinforcement agents. E and BP particles as dual reinforcement with various compositions were combined. The E/BP mixture was then embedded on a polymer matrix composing a resin/hardener mixture in a 1:1 ratio. As a standard, brake pads using a single reinforcement of E and BP particles were also fabricated. Physical properties (i.e. particle size, surface roughness, morphology, and density), as well as mechanical properties (i.e. hardness, wear rate, and friction coefficient properties) were investigated. It was observed that using dual reinforcements was preferable (compared to using single reinforcements) because they had a synergistic effect on the mechanical properties of the brake pad. The best mechanical properties were found in dual reinforcements of brake pad specimens using E/BP particles with a higher BP ratio in which the value of the stiffness test, puncture test, wear rate, and coefficient of friction were 4.5 MPa, 86.80, 0.093×10-4 g/s.mm2, and 1.67×10-4, respectively. A high BP particle ratio played a dominant role in dual reinforcements, increasing the resin's bonding ability and resulting in good adhesion between the reinforcement and matrix. When compared to commercial brake pads, the brake pad specimens fabricated in this study met the standards. The techno-economic analysis also confirmed the prospective production of brake pads from E and BP particles (compared to commercial brake pads). From this research, it is expected that environmentally friendly and low-cost brake pads can be used to replace the dangerous friction materials.